Inference of differentiation time for single cell transcriptomes using cell population reference data - Na Sun (Nature Portfolio, 2017)
Single cell transcriptome data can be used to determine developmental lineage trajectories. Here the authors map single cell transcriptomes onto a differentiation trajectory defined by cell population transcriptomes and show that cell cycle regulators have a role in differentiation timing.